Der Verlust der Eindeutigkeit. Zur Krise päpstlicher Autorität im Kampf um die Cathedra Petri - Müller, Harald (Schriften des Historischen Kollegs, 2017)
The struggle of the Antipopes multiplied the structures of the medieval church from the top down. This study focuses on this temporary blurring of the papal hierarchy and examines the mechanisms of duplication, assertions, and attributions of authority from historical, church historical, ecclesiastic, ceremonial, and historiographic perspectives.